Single vs. reimplant programs for finishing steers - Riley, Jack G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Finishing yearling beef steers were used to compare various implant programs in a 167-day trial. All implant programs increased daily gain ranging from 6.6 to 25.4% over non-implanted controls and improved feed efficiency ranging from .5 to 13.9%. Steers implanted with Ralgro® initially and reimplanted 75 days later with Synovex-S gained the fastest and most
Keywords: Beef; Implant; Gain